2016
DOI: 10.1007/s00701-016-2839-8
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted coil embolization of challenging intracranial aneurysms: initial and mid-term results with low-profile ACCLINO devices

Abstract: Stent-assisted coil embolization with ACCLINO stents in single or dual configurations is a feasible treatment option for challenging intracranial aneurysms. Follow-up results are encouraging; techniques were effective in complex cases and there were no clinically significant adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…In three retrospective studies published on the outcome of the CC Acclino stent and a larger contemporary series regarding the smaller BR stents (Leo Baby and LVIS Jr), the rate of death or permanent neurologic complications ranged from 0% to 7% and 2.4% to 3.8%, respectively. 15,2226 Although the rate of acceptable (RRS 1 and 2) aneurysm occlusion in our study was similar to the results reported in these manuscripts, the rate of neck remnants at final follow-up was higher in our study. One plausible explanation for this discrepancy may be the larger pore size and gator backing, which are known characteristics of the OC design.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In three retrospective studies published on the outcome of the CC Acclino stent and a larger contemporary series regarding the smaller BR stents (Leo Baby and LVIS Jr), the rate of death or permanent neurologic complications ranged from 0% to 7% and 2.4% to 3.8%, respectively. 15,2226 Although the rate of acceptable (RRS 1 and 2) aneurysm occlusion in our study was similar to the results reported in these manuscripts, the rate of neck remnants at final follow-up was higher in our study. One plausible explanation for this discrepancy may be the larger pore size and gator backing, which are known characteristics of the OC design.…”
Section: Discussionsupporting
confidence: 90%
“…It is unlikely that the Atlas stent has a considerable flowdiverting effect. Another explanation is that a portion of patients were treated with dual (X, Y, telescopic) stenting in these series, as well as with other devices during the same session (e.g., balloons and intrasaccular flow diverters in the reports on Acclino stents), 22,24 which increased the angiographic occlusion rate in these reports and precluded a pure assessment of the effects of the specific stent.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, immediate complete obliteration (RROC I-II) was achieved in 89.6% of the cases, similar to what has been described by Behme et al [5]. Table 3 summarizes the largest cases series (≥2 cases) describing Y-stentassisted coil embolization [4,5,[14][15][16][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 61%
“…The authors emphasize the closed-cell design of the Acclino stent with an electropolished surface, which theoretically decreases thrombogenicity. However, this design decreases stent conformability and enhances angular remodeling [15]. Similarly, Kabbasch et al [16] described 3 cases of Y-stenting with the Acclino stent, with a 33% complication rate: 1 IST, which resolved with IA GPIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation